2021
DOI: 10.1016/j.nbscr.2021.100068
|View full text |Cite
|
Sign up to set email alerts
|

A review of the current state of knowledge on sex differences in sleep and circadian phenotypes in rodents

Abstract: Sleep is a vital part of our lives as it is required to maintain health and optimal cognition. In humans, sex differences are relatively well-established for many sleep phenotypes. However, precise differences in sleep phenotypes between male and female rodents are less documented. The main goal of this article is to review sex differences in sleep architecture and electroencephalographic (EEG) activity during wakefulness and sleep in rodents. The effects of acute sleep deprivation on sleep duration and EEG ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 108 publications
(318 reference statements)
0
20
0
Order By: Relevance
“…In several of our assays, female data appear more variable than males. This could be due to influences of sex-hormone cycling, which are known to influence sleep [ 97 ] and motivated behaviors [ 98 ]. Likewise, THC is lipophilic and can be stored in adipose tissue [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…In several of our assays, female data appear more variable than males. This could be due to influences of sex-hormone cycling, which are known to influence sleep [ 97 ] and motivated behaviors [ 98 ]. Likewise, THC is lipophilic and can be stored in adipose tissue [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, we only used male mice for sleep analysis in the present study since RBD is generally more common in males than in females. The previous study analyzing WT mice inoculated with α-syn PFFs into the CNS reported that male PFFs-injected mice developed more severe α-syn pathology than female ones [ 19 ], while there was no significant difference in REM sleep amounts between the sexes [ 20 ]. Future research should be done on both sexes to understand the disease in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…For the IL-6 knockout (KO) group, eight-week-old IL-6 -/- male mice from the Laboratory of Molecular Immunology and Embryology, Transgenose Institute, Centre National de la Recherche Scientifique (CNRS) were bred onto a C57BL/6 background and used for the other experimental group. The male gender was used to avoid the influence of the hormonal cycle of female mice since the responses of the circadian cycle can suffer interference ( 17 ). The Ethics Committee of the University of Sao Paulo (I.D.…”
Section: Methodsmentioning
confidence: 99%